The Effect of Addition Amount of Chromium Iron on the Bonding Strength between Alloy Steel Surfacing Layer and Steel Base Metal - Fei Huang (Archives of Metallurgy and Materials)
Fe-C-Cr-Nb alloy steel surfacing layers with different contents of C and Cr were prepared on 45 steel base metal by selfshielded flux-cored wires with distinct amounts of high carbon chromium iron addition and melt arc surfacing. The composition and microstructure changes of the surfacing layer were tested and analyzed. The surfacing test plate was processed into a pulling specimen, and the bonding strength between the surfacing layer and the 45 steel base metal was tested with a self-designed pulling test method. The fracture location of the pulling specimen and fracture characteristics were observed by a metallurgical microscope and a scanning electron microscope. The result shows that with the increase of the amount of high carbon chromium iron added to flux-cored welding wire, the content of C and Cr in the surfacing layer increases, and the NbC hard phase disperses. The microstructure of the steel matrix changes from mixed martensite + residual austenite to high carbon martensite + residual austenite, and then independent austenite appears. The hardness of the surfacing layer first increases and then decreases. The bonding strength between the surfacing alloy and the 45 steel base metal first decreases and then increases, and the fracture location is at the bottom of the surfacing layer or the fusion zone with mostly quasi-cleavage characteristics. When the additional amount of high carbon chromium iron reaches 13%, thee pulling specimen exhibits significant deformation with the highest bonding strength, and the fracture is close to the fusion line, where there are numerous tearing edges and shallow dimples.